Occurrence of Neglected Picobirna Virus in Buffalo Calves Associated with Diarrhoea - Prasad, Meenakshi; Brar, Basanti; Ikbal,; Ranjan, Koushlesh; Misri, Jyoti (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Picobirna viruses (PBVs) thought to be neglected viruses, are emerging as causative agents of viral gastrointestinal infections in human and other animal species with enteritis. In the present study, a total of 408 fecal samples of diarrheic buffalo calves of under age of 2 months were collected from different locations in Haryana. These samples were preliminarily screened for PBV by RNA polyacrylamide gel electrophoresis (RNA-PAGE). The RNA-PAGE positive samples were further confirmed by RT-PCR using RdRp gene specific primer pair PicoB25 (+) and PicoB43 (-) for amplification of genogroup I PBV that generated an amplicon of 201 bp. Out of 408 buffalo calves fecal samples, 52 (13%) samples were found positive for genogroup 1(GGI) PBV using RT-PCR. Genogroup II (GGII) specific primer generating 369 bp product size did not show amplification in any of the samples. The results suggested occurrence of PBV in Haryana State with predominance of GGI PBV. To the best of our knowledge, this is the first report of detection as well as occurrence of GGI picobirna virus among diarrheic buffalo calves in Haryana State.
Keywords: Buffalo calves; Bisegmented dsRNA genome; Genogroup; RT-PCR,; Viral